2019
DOI: 10.1016/j.exer.2019.01.018
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome in NMDA-induced retinal excitotoxicity

Abstract: N-methyl-D-aspartate (NMDA)-induced excitotoxicity is an acute form of experimental retinal injury as a result of overactivation of glutamate receptors. NLRP3 (nucleotide-binding domain, leucine-rich-repeat containing family, pyrin domain containing-3) inflammasome, one of the most studied sensors of innate immunity, has been reported to play a critical role in retinal neurodegeneration with controversial implications regarding neuroprotection and cell death. Thus far, it has not been elucidated whether NMDA-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 72 publications
2
19
0
Order By: Relevance
“…In addition, the anti-inflammatory agent indomethacin has been reported to improve cognitive impairments by inhibiting microglia activation and reversing NMDAR dysfunction in aged rats [21]. On the other hand, another study has showed that NMDA-induced retinal excitotoxicity could trigger microglia recruitment and IL-1β production [36]. In our study, we found that anesthesia and surgery induced neuroinflammation and NMDAR overactivation.…”
Section: Discussionsupporting
confidence: 48%
“…In addition, the anti-inflammatory agent indomethacin has been reported to improve cognitive impairments by inhibiting microglia activation and reversing NMDAR dysfunction in aged rats [21]. On the other hand, another study has showed that NMDA-induced retinal excitotoxicity could trigger microglia recruitment and IL-1β production [36]. In our study, we found that anesthesia and surgery induced neuroinflammation and NMDAR overactivation.…”
Section: Discussionsupporting
confidence: 48%
“…Light-induced retinopathy showed an increase in NLRP3 after one-month [103], which was alleviated by the deletion of Ccr2 [103], and treatment with monomethyl fumarate [104]. NMDA-induced retinal excitotoxicity also resulted in a time-dependent increase of retinal NLRP3 mRNA [105], while TXNIP knockout in Müller cell culture prevented NLRP3 production [106]. Meanwhile, a transgenic mouse with P23H on Nlrp3 −/− background had reduced cone cell death [107].…”
Section: Nod-like Receptors In the Ocular Tissuesmentioning
confidence: 99%
“…Discovering potential downstream mediators of the Norrin-mediated protection of retinal neurons via Lif, would further contribute to the understanding of this signaling pathway. Finally, after induction of retinal excitotoxic damage, the role of reactive microglia is being discussed [47,48]. Therefore, the exploration of the effect of Norrin on microglia cells following acute retinal damage would open novel insights in Norrin-mediated neuroprotection of the retina.…”
Section: Discussionmentioning
confidence: 99%